Potential efficacy of preparations derived from Phaseolus vulgaris in the control of appetite, energy intake, and carbohydrate metabolism - Mauro AM Carai; Noemi Fantini; Barbara Loi; et al (Diabetes, Metabolic Syndrome and Obesity, 2009)
Mauro AM Carai1, Noemi Fantini1, Barbara Loi1, Giancarlo Colombo1, Antonella Riva2, Paolo Morazzoni21C.N.R. Institute of Neuroscience, Cagliari, Italy; 2Indena SpA, Milan, ItalyAbstract: Preclinical data on extracts of and preparations derived from beans of Phaseolus vulgaris are reviewed as potential remedies for use in controlling food consumption, body weight, lipid accumulation, and glycemia. A growing body of evidence suggests that acute and chronic administration of P. vulgaris derivatives reduces food intake (including highly palatable foods), body weight, lipid deposit, and glycemia in rats exposed to multiple experimental procedures. Two possible lectin-mediated mechanisms of action have been proposed: (a) inhibition of α-amylase, resulting in a reduced carbohydrate metabolism and absorption; (b) phytohemoagglutinininduced modulation of the activity of cholecystokinin and glucagon-like peptides, resulting in a reduced appetite. Preliminary clinical data, as well as reports focusing on the use of several traditional medicines, apparently extend these findings to humans. Should these initial clinical data be confirmed by future surveys, P. vulgaris derivatives might constitute novel remedies for the treatment of obesity and metabolic syndrome. Future studies are also expected to identify active structures leading to the development of new pharmaceutical agents.Keywords: Phaseolus vulgaris extracts and derivatives, food intake, body weight, lipid accumulation, glycemia, obesity, diabetes, metabolic syndrome